2014
DOI: 10.2320/matertrans.m2013388
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Two-Step Aging on Cluster Formation in Al–Mg–Si Alloys

Abstract: The change in the state of a MgSi cluster with pre-aging at 363 K, followed by aging at 303 or 323 K, was studied by means of a tensile test, three-dimensional atom probe (3DAP), and differential scanning calorimetry (DSC) measurements. MgSi clusters formed during isothermal aging (one-step aging) at 363 K after solution heat treatment were different from the ones formed at 303 and 323 K. Furthermore, during aging at 303 and 323 K following pre-aging at 363 K (two-step aging), the clusters that were originally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…However, no study has yet veri ed this observation. Results of DSC measurements reported in a previous paper 7) reveal that the exothermic peaks at 363, 530, and 585 K for the as-quenched specimen as shown in Fig. 5(a) indicate the formation of low-temperature clusters, β ′′ precipitates, and β ′ precipitates, respectively.…”
Section: Strength and Elongation After Long-term Agingmentioning
confidence: 63%
See 4 more Smart Citations
“…However, no study has yet veri ed this observation. Results of DSC measurements reported in a previous paper 7) reveal that the exothermic peaks at 363, 530, and 585 K for the as-quenched specimen as shown in Fig. 5(a) indicate the formation of low-temperature clusters, β ′′ precipitates, and β ′ precipitates, respectively.…”
Section: Strength and Elongation After Long-term Agingmentioning
confidence: 63%
“…5(b)) shows that the exothermic peaks at 363, 530, and 585 K disappeared and a new exothermic peak appeared at 567 K; no such new exothermic peak was observed for the as-quenched alloy. We assumed that the endothermic peak observed at around 500 K was similar to the peak observed in an alloy with high-temperature clusters in a previous study 7) , although the origin of this peak remains to be understood. It was reported that when an Al-Mg-Si alloy was aged at 363 K for a long time following solution heat treatment, the exothermic peaks corresponding to the formation of low-temperature clusters and β ′′ precipitates decreased and the peak corresponding to the formation of β ′ precipitates shifted to a lower temperature 7) .…”
Section: Strength and Elongation After Long-term Agingmentioning
confidence: 67%
See 3 more Smart Citations